An applied research model for the sport sciences - Bishop, D. (Sports Medicine, 2008)
Sport science can be thought of as a scientific process used to guide the practice of sport with the ultimate aim of improving sporting performance. However, despite this goal, the general consensus is that the translation of sport-science research to practice is poor. Furthermore, researchers have been criticised for failing to study problems relevant to practitioners and for disseminating findings that are difficult to implement within a practical setting. This paper proposes that the situation may be improved by the adoption of a model that guides the direction of research required to build our evidence base about how to improve performance.